2011
DOI: 10.1007/jhep12(2011)001
|View full text |Cite
|
Sign up to set email alerts
|

Non-standard antineutrino interactions at Daya Bay

Abstract: We study the prospects of pinning down the effects of non-standard antineutrino interactions in the source and in the detector at the Daya Bay neutrino facility. It is well known that if the non-standard interactions in the detection process are of the same type as those in the production, their net effect can be subsumed into a mere shift in the measured value of the leptonic mixing angle θ 13 . Relaxing this assumption, the ratio of the antineutrino spectra measured by the Daya Bay far and near detectors is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…For example, NSI effects have previously been studied for the accelerator-based neutrino oscillation experiments MINOS and OPERA [3,4], atmospheric neutrino experiments [5][6][7], reactor neutrino experiments [8][9][10], and a future neutrino factory [11][12][13][14][15]. In this work, we investigate neutrino flavor transition probabilities based on standard neutrino oscillations and NSIs as sub-leading effects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, NSI effects have previously been studied for the accelerator-based neutrino oscillation experiments MINOS and OPERA [3,4], atmospheric neutrino experiments [5][6][7], reactor neutrino experiments [8][9][10], and a future neutrino factory [11][12][13][14][15]. In this work, we investigate neutrino flavor transition probabilities based on standard neutrino oscillations and NSIs as sub-leading effects.…”
Section: Introductionmentioning
confidence: 99%
“…While earlier studies [32][33][34] demanded that reactor experiments bound the NSI parameters ǫ eµ and ǫ eτ , recent analysis [35,36] showed that Daya Bay experiment cannot constrain the flavor-changing NSI parameters because of their strong correlation with the reactor angle θ 13 . It can, however, bound |ǫ ee | < O(10 −2 ), when the parameter is considered to be real, and a normalization error in the neutrino flux is taken into account.…”
Section: Neutrino Oscillationsmentioning
confidence: 99%
“…To my knowledge, there exist only three studies with reactor neutrinos and NSIs. (i) A combined study of the performance of reactor and superbeam neutrino experiments in the presence of NSIs [37], (ii) a study of only reactor neutrino experiments and NSIs [38], and (iii) NSIs at the Daya Bay experiment [39]. In the second study, it turns out that the measured value for θ 13 could be a combination of the fundamental value for θ 13 and effects of NSI parameters, whereas in the third study, one can estimate the effects of the NSIs in the determination of the standard oscillation parameters θ 13 and ∆m 100 GeV neutrino factory could probe flavor-changing neutrino interactions of the order of |ε| 10 −4 at 99 % C.L.…”
Section: Phenomenology Of Nsismentioning
confidence: 99%